How do MNEs shape their international strategic alliances to facilitate higher alliance performance? Absorptive capacity as an antecedent - Chen, Zhong; Zheng, Langping; Peng, Michael Yao-Ping; Shao, Lijin (Frontiers in Psychology, 2022)
The international strategic alliance in international marketing is international social network to realize superior performance. This requires firms to increasingly consolidate international relationship with foreign partners. Knowledge acquisition and integration by absorptive capacity as an antecedent for international strategic alliance is understudied. This study aims to explore the relationship between absorptive capacity and international strategic alliance, and their impact on the international performance of multinational enterprises (MNEs). This study empirically verifies the research framework from 223 Taiwanese MNEs. In term of structural model, researchers conduct PLS-SEM to verify the hypotheses in this study. The results confirm previous studies that indicate a positive relationship among absorptive capacity, international strategic alliance, and international performance. The results also indicate that international explorative and exploitative alliance fits mediate the relationship between absorptive capacity and international performance.